PENGARUH KOMPOSISI MEDIA TANAM TERHADAP HASIL DAN KUALITAS ICROGREEN SELADA (Lactuca Sativa L) - Indra, Indra; Theresa Dwi Kurnia (Bajang Institute, 2024)
Microgreens is a plant that can be harvested within 7-21 day after seedling and has a higher vitamin content when compared to mature plants. Various kinds pf plants can be cultivated in microgreens, one of which is lettuce. In microgreens cultivation, the planting media used should be sterile and have a high ability to absorb. This study aims to determine the effect of planting media comopsition on day yield and quality of microgreens lettuce. This research was conducted in the greenhouse of Science Techno Park (STP) Satya Wacana Christian University, in April 2024. The design used is a randomised group design (RAK), with 1 factorial (planting media), which consist of 5 treatments, namelly: P1 (Soil), P2 (Soil + Cocopeat), P3 (Soil + Rice Husk), P4 (Soil + Husk Charcoal), P5 (Soil + Vermiculit) which were repeated 5 times. Parameters observed in this study includ plant hieght, number of leaves, chlorophyll content, vitamin c content and dry weight. The result showed that the composition of planting media had a significant effect on plant height and dry weight, planting media P4 (soil + Husk Charcoal) gave the best result with an averege plant height of 6,48(cm) and dry weight of 0,682 (g). However, it did not significantly effect the number of leaves, chlorophyll content and vitamin C content